A combination of restudy and retrieval practice maximizes retention of briefly encountered facts - Ashby, Stefania R.; Zeithamova, Dagmar (Frontiers in Cognition, 2023)
Is retrieval practice always superior to restudy? In a classic study by Roediger and Karpicke (2006a) long-term retention of information contained in prose passages was found to be best when opportunities to restudy were replaced with opportunities to self-test. We were interested whether this striking benefit for repeated testing at the expense of any restudy replicates when study opportunities are brief, akin to a single mention of a fact in an academic lecture. We were also interested in whether restudying after a test would provide any additional benefits compared to restudying before test. In the current study, participants encountered academically relevant facts a total of three times; each time either studied (S) or self-tested (T). During study, participants predicted how likely they were to remember each fact in the future. During self-test, participants performed covert cued recall and self-reported their recall success. Final test followed immediately or after a delay (Experiment 1: two days, Experiment 2: seven days). Contrary to prior work, long-term memory was superior for facts the were restudied in addition to self-tested (SST > STT = SSS). We further investigated whether restudy after a test (STS) provides additional benefits compared to restudy before test (SST) but found comparably high delayed recall in both conditions. Finally, exploratory analyses indicated that restudy after test improved the accuracy of participants’ subjective predictions of encoding success. Together, results show that under some circumstances, balancing repetition and testing can allow for more information to be learned and retained.